A3_6 Hot Stuff - Yeo, Adam; Routledge, Hannah; Lewis, Jacob; Meggi, Dikshita (Physics Special Topics, 2021)
In the hit game ”Minecraft”, lava poses a huge threat to your progress as well as being a valuable resource. In this paper we analyse how lava is programmed into Minecraft and attempt to categorise it as a mafic or felsic lava. Since lava in the game moves at around 2 3ms−1 , the lava shares similar properties to a basaltic lava at around 1160◦ Celsius, with a coefficient of viscosity of around 6.82x102P as and is therefore most likely mafic. This calculation however assumes the lava flow in game is non-turbulent and does not explain why obsidian is formed when the lava interacts with water.